2013
DOI: 10.1118/1.4800642
|View full text |Cite
|
Sign up to set email alerts
|

MTF behavior of compressed sensing MR spectroscopic imaging

Abstract: The authors have shown that in certain cases small variations in the reconstruction weights yield a measureable effect on the CS reconstructed images, particularly with regard to MTF. Furthermore, it was found that peak SNR affects CS-MRSI MTF especially at higher wavelet reconstruction weights. Accordingly, prior knowledge of the expected peak SNR is essential to optimize the CS reconstruction process. Their phantom-MTF technique provides a quantitative performance measure of MRSI sequences, through which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…In such cases, the reconstruction algorithm would need to be tailored to ensure a reliable representation of low‐concentration metabolites at higher accelerations, especially when the acquired MRSI data are SNR limited. Other areas of ongoing research involve determining the best pseudo‐random undersampling mask tailored to MRSI at each acceleration factor, and investigating the potential impact of CS reconstruction on the low spatial resolution in MRSI …”
Section: Doing More With Less Data: Fast Mrsi With Undersamplingmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, the reconstruction algorithm would need to be tailored to ensure a reliable representation of low‐concentration metabolites at higher accelerations, especially when the acquired MRSI data are SNR limited. Other areas of ongoing research involve determining the best pseudo‐random undersampling mask tailored to MRSI at each acceleration factor, and investigating the potential impact of CS reconstruction on the low spatial resolution in MRSI …”
Section: Doing More With Less Data: Fast Mrsi With Undersamplingmentioning
confidence: 99%
“…Other areas of ongoing research involve determining the best pseudo-random undersampling mask tailored to MRSI at each acceleration factor, 143 and investigating the potential impact of CS reconstruction on the low spatial resolution in MRSI. 144…”
Section: Figure 11mentioning
confidence: 99%
“…From the artifact power analysis, it is clear that the 2D-CS method is relatively sensitive to the degree of undersampling of k-space. Heikal et al 25 have shown that undersampling in compressed sensing causes quantifiable loss in spatial frequency response (as described by its modulation transfer function) in reconstructed image. At low acceleration, the sampling pattern still has a significant amount of sampled data points in the high frequency regions (Fig.…”
Section: A Performance Dependence On Acceleration Factors-high Snrmentioning
confidence: 99%
“…Recently, a method has been introduced in the literature to quantify the MTF of MRSI scans and to provide a quantitative measure of the cost and benefit of CS-MRSI. 6 At first glance, the validity of MTF as a metric for linear systems would appear to be at odds with the nonlinearity of the CS reconstruction. However, previous work has shown that when the reconstruction weights are carefully chosen, a robustness of the spatial frequency response of the system with different noise levels can be established.…”
Section: Introductionmentioning
confidence: 99%